ダイ5ジ ノ ナンキョク チイキ カンソクタイ カイヨウ ブモン ブツリ カンケイ ホウコク - 堀, 定清; ホリ, サダキヨ; HORI, Sadakiyo (国立極地研究所, 1962)
P(論文) 第5次南極地域観測(1960年11月～1961年5月)において海洋部門の船上観測の一部としてBT観測および各層観測を行なった.BT観測は原則として,ケープタン・南極間は1日2回,その他においては1日1回行なった.各層観測は南極洋において7点,帰路のインド洋において2点行なった(Fig. 1).これらの観測の結果はFigs. 2～7に示した通りであるが,本文においては,主として物理的海洋学の立場からこれらの観測結果を記述した. Bathythermograph and serial observations were performed on board the "SOYA" of the Japanese Antarctic Research Expedition (J.A.R.E.) as one of the research projects during the period of the expedition (Nov. 1960-May 1961). Bathythermograph observations were normally carried out once a day between Tokyo and Cape Town and twice a day between Cape Town and the Antarctic Region while the ship was at sea. Five hydrographic stations were occupied in the Antarctic Region, two after leaving the icy sea toward Cape Town and two in the northeastern part of the Indian Ocean on the way back to Singapore. Results of these observations are shown in the Figures and described mainly from the standpoint of physical oceanography. departmental bulletin paper